Novice Shooters With Lower Pre-shooting Alpha Power Have Better Performance During Competition in a Virtual Reality Scenario - Pereira, Michael; Argelaguet, Ferran; Millán, José del R.; Lécuyer, Anatole (Frontiers in Psychology, 2018)
Competition changes the environment for athletes. The difficulty of training for such stressful events can lead to the well-known effect of 'choking' under pressure, which prevents athletes from performing at their best level. To studying the effect of competition on the human brain, we recorded pilot electroencephalography (EEG) data while novice shooters were immersed in a realistic virtual environment representing a shooting range. We found a differential between-subject effect of competition on mu [8-12 Hz] oscillatory activity during aiming; compared to training, the more the subject was able to desynchronize his mu rhythm during competition, the better was his shooting performance. Because this differential effect could not be explained by differences in simple measures of the kinematics and muscular activity, nor by the effect of competition or shooting performance per se, we interpret our results as evidence that mu desynchronization has a positive effect on performance during competition